2017
DOI: 10.1111/oik.03956
|View full text |Cite
|
Sign up to set email alerts
|

Growth strategy, phylogeny and stoichiometry determine the allelopathic potential of native and non‐native plants

Abstract: Secondary compounds can contribute to the success of non-native plant species if they reduce damage by native herbivores or inhibit the growth of native plant competitors. However, there is opposing evidence on whether the secondary compounds of non-native plant species are stronger than those of natives. This may be explained by other factors, besides plant origin, that affect the potential of plant secondary compounds. We tested how plant origin, phylogeny, growth strategy and stoichiometry affected the alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 98 publications
(150 reference statements)
6
20
0
Order By: Relevance
“…The total phenolic content (TPC) of L. hexapetala leaves observed in this study is very close to the TPC recently observed byGrutters et al (2017) that identified Ludwigia species as macrophytes with a high allelopathic potential. The total phenolic content (TPC) of L. hexapetala leaves observed in this study is very close to the TPC recently observed byGrutters et al (2017) that identified Ludwigia species as macrophytes with a high allelopathic potential.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…The total phenolic content (TPC) of L. hexapetala leaves observed in this study is very close to the TPC recently observed byGrutters et al (2017) that identified Ludwigia species as macrophytes with a high allelopathic potential. The total phenolic content (TPC) of L. hexapetala leaves observed in this study is very close to the TPC recently observed byGrutters et al (2017) that identified Ludwigia species as macrophytes with a high allelopathic potential.…”
supporting
confidence: 89%
“…Non-toxic M. aeruginosa was strongly inhibited (49%), in agreement with a recent study highlighting the strong inhibitory effect of L. hexapetala aqueous extracts on the cyanobacterium Dolichospermum flos-aquae(Grutters et al, 2017). Non-toxic M. aeruginosa was strongly inhibited (49%), in agreement with a recent study highlighting the strong inhibitory effect of L. hexapetala aqueous extracts on the cyanobacterium Dolichospermum flos-aquae(Grutters et al, 2017).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the previous speculation that fully submerged macrophytes develop stronger allelopathy, as they face the strongest light and space competition with higher plants, phytoplankton, or periphyton (Gross 2003). This does not, however, support Grutters et al (2017), who found higher phenolic content in emergent macrophytes compared to submerged macrophytes, and consequently hypothesized stronger allelopathy in emergent macrophytes.…”
Section: Macrophytes Of Different Growth Forms Vary In Effects On Watsupporting
confidence: 85%